Motivation of a slow learner in an elementary school - Febriyani, Amalia Rizki; Haerudin, Deden (CV. Mitra Palupi, 2020)
Background: Â Low intellect makes slow learner students feel inferior and feel that they will never learn. As a consequence, slow learner students, sometimes, have no motivation to learn in them. Motivation has an important role in children's learning activities. It can be said that motivation is the driving force for children's activities. One of them is MF, a student identified as a slow learner by their class teacher.Purpose: For this reason, this study aims to determine the extent to which the causes of changes in MF motivation levels in the teaching and learning activities.Design and methods: This research uses a case study method. This research was conducted on one of the students identified by the class teacher as a slow learner. This research data using observation, interviews, and documentation. The collected data were grouped based on various factors that influenced learning motivation initiated by Dimyati and Mudjiono. Validation is done by triangulating data sources used to test the credibility of the data by checking the data that has been obtained through several sources.Results: The results of this study reveal 2 out of 6 things that influence the level of learning motivation to encourage MF to continue learning, namely ownership of ideals and increasing personal abilities.